Cytometric analysis of cell suspension generated by cavitron ultrasonic surgical aspirator in pediatric brain tumors - Vaskova, Martina; Tichy, Michal; Zamecnik, Josef; Liby, Petr; Kuzilkova, Daniela; Vicha, Ales; Hrabeta, Jan; Kalina, Tomas; Stary, Jan; Hrusak, Ondrej (Journal of neuro-oncology, 2019)
PURPOSE: The aim of this study was to test the possibility of using specimens obtained by a cavitron ultrasonic surgical aspirator (CUSA) in flow and mass cytometry investigations of pediatric brain tumors. METHODS: CUSA specimens obtained from 19 pediatric patients with brain tumors were investigated. Flow and mass cytometry methods were applied to analyze the composition of material collected using the CUSA. Cell suspensions were prepared from CUSA aspirates. Then sample viability was assessed by conventional flow cytometry and subsequently stained with a panel of 31 metal-labeled antibodies. RESULTS: Viability assessment was performed using conventional flow cytometry. Viability of cells in the acquired samples was below 50% in 16 of 19 cases. A mass cytometry investigation and subsequent analysis enabled us to discriminate brain tumor cells from contaminating leukocytes, whose proportions varied across the specimens. The addition of the viability marker cisplatin directly into the mass cytometry panel gave the means to selecting viable cells only for subsequent analyses. The proportion of non-viable cells was higher among tumor cells compared leukocytes. CONCLUSIONS: When the analysis of the tumor cell immunophenotype is performed with markers for determining viability, the expression of the investigated markers can be evaluated. Suitable markers can be selected by high-throughput methods, such as mass cytometry, and those that are diagnostically relevant can be investigated using flow cytometry, which is more flexible in terms of time.
Keywords: Ultrasonic Therapy; cisplatina; průtoková cytometrie; Humans; analýza jednotlivých buněk; lidé; Biomarkers, Tumor; nádorové biomarkery; Brain Neoplasms; ultrazvuková terapie; Flow Cytometry; Neurosurgical Procedures; Leukocytes; Single-Cell Analysis; Cisplatin; nádory mozku; viabilita buněk; neurochirurgické výkony; leukocyty; Cell Survival